ELABORATION OF A RISK SCORE FOR CELIAC DISEASE SCREENING - Luiza Arregui Igarsaba; Mônica Maria Celestina de Oliveira; Daniele Botelho Vinholes (Demetra, 2019)
Objective: This study aims to elaborate a risk score that will aid in the screening of celiac disease, based on the risk factors already described in the literature. Methods: It is a case-control study with two groups: individuals who reported having celiac disease and individuals who reported not having celiac disease. For data collection, a questionnaire was elaborated based on the bibliographic review, answered online by the research participants. The data collected were entered in the Excel program and analyzed in the SPSS 23.0 program. Results: Among these questionnaires, 72 were cases (with celiac disease) and 54 controls (without celiac disease). There was a significant difference, with p-value of 0.005, among the scores of the group of cases, 7.09 (standard deviation: 1.47), and of the control group, 4.59 (standard deviation: 1.94). Discussion: The main benefit is that, with more studies, the celiac patient can initiate treatment early, reducing the risk of complications and associated comorbidities, and reduce the rate of death of undiagnosed or late diagnosed celiac patients. Conclusion: There is a significant difference between the risk scores, showing that the cases have a higher score in relation to the controls. It is important to make it clear that this score will be used only for screening study purposes and not for celiac disease diagnosis. DOI: 10.12957/demetra.2019.32905